Electric properties of Fe-doped Na0.5Bi0.5TiO3 ceramics in unpoled and poled state. (1st September 2020) - Suchanicz, J.; Wąs, M.; Nowakowska-Malczyk, M.; Jelen, P.; Konieczny, K.; Czaja, P.; Kluczewska-Chmielarz, K.; Sitko, D.; Kruzina, T.V.; Sokolowski, M.
ABSTRACT: The Fe-substituted Na0.5 Bi0.5 TiO3 (NBT) ceramics were prepared through solid-state reaction technique. X-ray diffraction analysis indicated the formation of perovskite structure with rhombohedral symmetry. It was found that 0.5 mol% Fe and 0.1 mol% Fe dopant concentration increases the depolarization temperature Td, Tm, the dielectric loss and electric conductivity. The effects can be mainly the result of free charges and ( F e T i ′ - V O ∙ ∙ ) ∙ microdipoles appearance due to Fe-introduced to NBT. It was shown that a prior electric field poling process changes the character of ε(T) and tanδ(T) plots, shifts of Td and Tm and slightly changes the Raman spectra. The effects are mainly caused by the reinforcement of polarization/domain ordering and by the partial transformation of tetragonal regions into rhombohedral phase by electric field.